Elucidating Organizational Readiness of K12 Schools in United States for Online Education - Najih Samin Ahmed; Cumhur Aydinli; Tim Saka (International Journal of Social Sciences & Educational Studies, 2022)
The main purpose of this study is to strategically map the organizational readiness of K12 schools in the USA for online education. Data for this study were collected using questionnaires. Of 500 teachers who were sent invitations in charter schools in the USA, 130 sent back their responses. Statistical analysis was performed using SPSS software. The results of the study show that variables such as cultural readiness, cognitive readiness, and stategic readiness were not fundamental variables, but were mediator variables. These varibales emerge over time as a consequence of school administrations’ IT strategies, technical and tight partnerships with IT companies, and directing their financial resources to online education. The study concludes that in order to be ready for online education, first of all, employees must be ready for it in a cognitive sense, and online education processes must become a culture within the organization.